2022
DOI: 10.1038/s42003-022-03965-x
|View full text |Cite
|
Sign up to set email alerts
|

Dementia with Lewy bodies post-mortem brains reveal differentially methylated CpG sites with biomarker potential

Abstract: Dementia with Lewy bodies (DLB) is a common form of dementia with known genetic and environmental interactions. However, the underlying epigenetic mechanisms which reflect these gene-environment interactions are poorly studied. Herein, we measure genome-wide DNA methylation profiles of post-mortem brain tissue (Broadmann area 7) from 15 pathologically confirmed DLB brains and compare them with 16 cognitively normal controls using Illumina MethylationEPIC arrays. We identify 17 significantly differentially meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted July 23, 2023. ; https://doi.org/10.1101/2023.07. 20.549825 doi: bioRxiv preprint have shown robust alterations in DNA methylation in a number of genes in different neurodegenerative diseases, in both the brain and blood, including Alzheimer's disease (AD) [23][24][25] , PD [26][27][28] and Dementia with Lewy bodies (DLB) 29 . Interestingly, associations have also been reported for secondary symptoms of these neurodegenerative disease, for example with psychosis symptoms in AD 30 or cognition in PD 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted July 23, 2023. ; https://doi.org/10.1101/2023.07. 20.549825 doi: bioRxiv preprint have shown robust alterations in DNA methylation in a number of genes in different neurodegenerative diseases, in both the brain and blood, including Alzheimer's disease (AD) [23][24][25] , PD [26][27][28] and Dementia with Lewy bodies (DLB) 29 . Interestingly, associations have also been reported for secondary symptoms of these neurodegenerative disease, for example with psychosis symptoms in AD 30 or cognition in PD 27 .…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation, which refers to the reversible addition of methyl groups to cytosines typically in a CpG dinucleotide, is the most studied epigenetic mechanism in neurological disorders 22 . Indeed, several studies have shown robust alterations in DNA methylation in a number of genes in different neurodegenerative diseases, in both the brain and blood, including Alzheimer's disease (AD) [23][24][25] , PD [26][27][28] and Dementia with Lewy bodies (DLB) 29 . Interestingly, associations have also been reported for secondary symptoms of these neurodegenerative disease, for example with psychosis symptoms in AD 30 or cognition in PD 27 .…”
Section: Introductionmentioning
confidence: 99%